Interferon–ribavirin therapy induces serum antibodies determining 'rods and rings' pattern in hepatitis C patients. Issue 12 (14th July 2014) - Novembrino, Cristina; Aghemo, Alessio; Ferraris Fusarini, Chiara; Maiavacca, Rita; Matinato, Caterina; Lunghi, Giovanna; Torresani, Erminio; Ronchi, Mariangela; Garlaschi, Maria Cristina; Ramondetta, Miriam; Colombo, Massimo
Summary A cytoplasmic antigen associated to inosine‐5'‐monophosphatedehydrogenase 2 eliciting specific antibodies (antirods and rings, RR) has been identified in patients with chronic hepatitis C who were exposed to pegylated interferon (PI) and ribavirin (RBV). The significance of anti‐RR in these patients merits to be investigated. Sera from 88 chronic hepatitis C virus (HCV)‐infected patients undergoing PI‐RBV therapy were analysed for the presence of RR pattern by indirect immunofluorescence on HEp‐2 substrate (Inova Diagnostics, San Diego, CA, USA). Anti‐RR antibodies developed de novo in 32 patients independently of any demographic and virological feature, but with a significant association with cumulative exposure to PI‐RBV (P = 0.0089; chi‐square test). RR pattern was significantly more frequent in relapsers than in patients achieving sustained virological response (56% vs 30%; P = 0.0282, chi‐square test). Anti‐RR titre ranged from 1:80 to 1:1280, but significantly declined following treatment cessation. Anti‐RR develop de novo in a substantial proportion of patients exposed to PI‐RBV in relation to the duration of treatment exposure. Further investigations are necessary to unravel the mechanisms leading to the formation of these autoantibodies.